2009
DOI: 10.1177/0091270008330160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food on the Pharmacokinetics and Pharmacodynamics of an Oral Ghrelin Agonist (ARD‐07) in Healthy Subjects

Abstract: ARD-07 (also known as EP01572) is a peptidomimetic growth hormone secretagogue that can be administered orally. The primary objective of this study is to determine the effects of a meal on the oral bioavailability of ARD-07 after a single oral dose (0.5 mg/kg). In addition, the pharmacodynamic effects (growth hormone release, insulin-like growth factor-1 concentrations) and the tolerability of ARD-07 are investigated in this open-label, randomized, crossover study. Sixteen healthy subjects (8 males, 8 females)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In human plasma, acylated ghrelin was found to disappear more quickly than total ghrelin, with elimination half‐lives of 9–13 and 27–31 min, respectively (Akamizu et al., 2004). A number of synthetic ghrelin agonists are currently being investigated, with compounds such as ARD‐07 (EP01572) showing a promising pharmacokinetic profile with regard to its significantly longer elimination half‐life and good tolerability in human subjects (Piccoli et al., 2007; MacLean et al., 2009).…”
Section: Ghrelin and Its Receptor(s)mentioning
confidence: 99%
“…In human plasma, acylated ghrelin was found to disappear more quickly than total ghrelin, with elimination half‐lives of 9–13 and 27–31 min, respectively (Akamizu et al., 2004). A number of synthetic ghrelin agonists are currently being investigated, with compounds such as ARD‐07 (EP01572) showing a promising pharmacokinetic profile with regard to its significantly longer elimination half‐life and good tolerability in human subjects (Piccoli et al., 2007; MacLean et al., 2009).…”
Section: Ghrelin and Its Receptor(s)mentioning
confidence: 99%
“…The short half–life is a major hurdle; also, the bioavailability of peptides can be reduced by food interactions. Food has recently been shown to markedly reduce the absorption of an orally available ghrelin agonist 28 . To overcome these problems for GLP–1, different strategies are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Food has recently been shown to markedly reduce the absorption of an orally available ghrelin agonist. 28 To overcome these problems for GLP-1, different strategies are possible. To deal with the short half-life, two classes of pharmaceutical agents have been developed: (i) longacting analogs (GLP-1 mimetics) and (ii) dipeptidyl peptidase IV inhibitors (incretin enhancers).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies using GHS have shown positive effects on appetite, body weight and body composition in healthy volunteers and in patients with cancer cachexia 12–18 and one such drug, anamorelin, has been recently approved for cachexia treatment in Japan 19 . Macimorelin, a novel, orally active GHS with similar GHSR‐1a binding affinity as ghrelin, is well‐tolerated as a single dose in healthy volunteers and individuals at risk for pituitary dysfunction 9,14,20–28 . It received approval from the US Food and Drug Administration (FDA) in 2017 and European Medicines Agency (EMA) in 2019 as a single dose for adult GH deficiency (AGHD) diagnosis 9,22,29 but has not been examined in repeated doses or in the cancer setting.…”
Section: Introductionmentioning
confidence: 99%